The Role of Counseling Media on Knowledge, Attitudes and Actions Women of Childbearing Age in IVA Examination at East Kolaka District - Harsup Moita, Putri; Sunarsih, Sunarsih; Fatmawati, Fatmawati (Waluya The International Science of Health Journal, 2023)
Introduction: Based on the 2019 of Regional Health Research, the early detection of cancer that has been carried out is the early detection of cervical cancer using the IVA method (Visual Inspection with Acetic Acid), which shows a decrease in IVA detection in each public health center and is still far from the national target of 100%. East Kolaka District is the area with the second lowest IVA examination rate at 0.08% while the first lowest IVA examination area is in Konawe District at 0.04% from 17 districts. Method: This type of research is experimental research, a pre-experimental design with Four Groups Pretest-Posttest research design, was used to examine the role of the counseling media to the knowledge, attitudes and actions of women childbearing age in the IVA examination in East Kolaka District. The sample size of the respondents was 186 people. Result: The Role models, FGDs, leaflets and whatsapp application had an effect on knowledge, attitudes and actions in the IVA examination in East Kolaka District. Conclusion: Looking at the average increase in the result shows that whatsapp media was more effective in increasing knowledge, attitudes and actions than the other three media.